2010
DOI: 10.1111/j.1467-789x.2009.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic surgery: an evolution through bariatric animal models

Abstract: Metabolic surgery was developed through the application and experience gained from bariatric or weight loss procedures. Much of our knowledge from the procedures comes from the study of animal models, where they have revealed anatomic feasibility, systemic physiological elements and cellular metabolic effects. The first generation of operation included the jejunoileal bypass and partial ileal bypass that led to the development of the current procedures including Roux-en-Y gastric bypass, biliopancreatic divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 116 publications
0
65
0
1
Order By: Relevance
“…11,58,59 Although, traditionally, surgery was considered to achieve weight loss through the malabsorption of food and restriction of stomach size, there is some discrepancy supporting the effects of stomach-pouch size or calorific malabsorption other than for a minority of procedures (such as the biliopancreatic diversion). 11,60 Surgery does, however, achieve a sustained decrease in caloric intake, 61,62 which has a long-standing association with decreased carcinogenesis in several experimental models that span over a century of research. 63,64 One study has revealed that the Roux-en-Y gastric bypass operation can decrease daily calorie intake by 1479 Kcal/day so that patients only consume 1341 Kcal/day.…”
Section: Decreased Obesity Through Weight Lossmentioning
confidence: 99%
See 3 more Smart Citations
“…11,58,59 Although, traditionally, surgery was considered to achieve weight loss through the malabsorption of food and restriction of stomach size, there is some discrepancy supporting the effects of stomach-pouch size or calorific malabsorption other than for a minority of procedures (such as the biliopancreatic diversion). 11,60 Surgery does, however, achieve a sustained decrease in caloric intake, 61,62 which has a long-standing association with decreased carcinogenesis in several experimental models that span over a century of research. 63,64 One study has revealed that the Roux-en-Y gastric bypass operation can decrease daily calorie intake by 1479 Kcal/day so that patients only consume 1341 Kcal/day.…”
Section: Decreased Obesity Through Weight Lossmentioning
confidence: 99%
“…Here, the surgical patients had a 5 times higher remission rate for diabetes compared with medical controls, and weight loss was the principal predictor of diabetes remission. 31,57 The mechanisms for weight loss after metabolic surgery are muiltifactorial 11,12 and include the modulation of gut hormones that lead to alterations in appetite, hunger, dietary feeding behavior, and, more recently, taste modulation in addition to alterations in metabolic rate and resting energy expenditure. 11,58,59 Although, traditionally, surgery was considered to achieve weight loss through the malabsorption of food and restriction of stomach size, there is some discrepancy supporting the effects of stomach-pouch size or calorific malabsorption other than for a minority of procedures (such as the biliopancreatic diversion).…”
Section: Decreased Obesity Through Weight Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…19 SG has a similar hypoglycemic effect to Roux-en-Y bypass. 4 JIB was a widely performed procedure for morbid obesity during the 1970s, and it led to intestinal malabsorption for reducing weight and decreasing blood glucose; however, because of the high morbidity rates, its popularity declined, and most surgeons no longer perform the operation.…”
Section: Discussionmentioning
confidence: 66%